Perspective: Raman spectroscopy for detection and management of diseases affecting the nervous system - Robertson, John L.; Sayed Issa, Amr; Senger, Ryan S. (Frontiers in Veterinary Science, 2024)
Raman spectroscopy (RS) is used increasingly for disease detection, including diseases of the nervous system (CNS). This Perspective presents RS basics and how it has been applied to disease detection. Research that focused on using a novel Raman-based technology—Rametrix® Molecular Urinalysis (RMU)—for systemic disease detection is presented, demonstrated by an example of how the RS/RMU technology could be used for detection and management of diseases of the CNS in companion animals.